Cultura e biodiversidade: uma comparação entre a gestão do Parque Nacional do Cabo Orange, no Brasil, e a do Parque Nacional da Vanoise, na França - Nádia Bandeira Sacenco Kornijezuk (Confins)
This article compares the management of two national parks: Cabo Orange National Park, in Brazil, and Vanoise National Park, in France. The regions in which these two national parks are located - the Brazilian Amazon and the French Alps, respectively - have an important global ecological value. Both Cabo Orange National Park and the Vanoise National Park have rare and remarkable ecosystems and, due to the complexity of their interactions, are threatened by global changes. The Cabo Orange National Park is presented in its regional context and its tourism. The Vanoise National Park is analyzed from the standpoint of tourism and France´s historical and geographical determinants. The comparison between the management of the Vanoise National Park and the Cabo Orange National Park shows that conservation requirements are similar, but their geopolitical and environmental contexts are different. On the one hand, France is more populous and its biodiversity is vastly impoverished. On the other hand, Brazil is a country of open spaces where biodiversity is, in many cases, the result of a natural evolutionary process. It was found that the Vanoise National Park has directed its administration to reconcile regional development and conservation of natural and cultural heritage, while the Cabo Orange National Parke guards its biodiversity in its most pristine expression possible.